Tissue factor gene expression in the adipose tissues of obese mice - Fahumiya Samad; Manjula Pandey; David J. Loskutoff (1998)
With advancements in stem cell technology, in vitro models using iPSC (induced pluripotent stem cells)-derived cardiomyocytes (iPSC-CM) and engineered heart tissues (EHT) can serve as powerful tools for disease modeling and drug screening. ...Fluorescent reporters of cardiac electrophysiology provide valuable information on heart cell and tissue function. However, motion artifacts caused by cardiac muscle contraction interfere with accurate measurement of fluorescence signals. Although drugs ...